HUBUNGAN FLEKSIBILITAS PERGELANGAN TANGAN TERHADAP KEMAMPUAN PASSING ATAS PADA PEMAIN BOLA VOLI BIMA SAKTI CLUB - Namira Ramadinah; Rusli Rusli; Sarifin G (Program Studi Ilmu Keolahragaan FIK UNM, 2022)
The purpose of this study was to determine whether there is a relationship between wrist flexibility and over-passing ability in volleyball players at the Bima Sakti Club. The type of research used is descriptive correlational, which aims to determine the relationship between several variables and how close the relationship is. The population in this study were members of the Bima Sakti Club as many as 17 people and the research sample was all members of the Bima Sakti Club (total sampling). The data analysis technique used is Descriptive Analysis, Data Normality Test, and Correlation Test. Based on data analysis, descriptive test results with wrist flexibility data obtained an average value (mean) of 87.63, a minimum value of 80.50, a maximum value of 94.00, a range value of 13.50, a standard deviation of 3.62. The data on the passing ability obtained an average value (mean) of 44.11, a minimum value of 22.00, a maximum value of 59.00, a range value of 37.00, a standard deviation of 12.74. The results of the normality test of wrist flexibility data obtained the Kolmogorov-Smirnov value of 0.433 and the Asymp value. Sig 0.992 (P>0.05). The data on the ability of passing over obtained the Kolmogorov-Smirnov value of 0.612 and the Asymp value. Sig 0.848 (P>0.05). The results of the correlation test of data analysis obtained the calculated correlation value (r) = 0.59 and P = 0.01 (P < 0.05). It means that there is a relationship between wrist flexibility and over-passing ability in volleyball players at the Bima Sakti Club.